O uso de plugins gratuitos e de código aberto em sistemas operacionais linux na produção musical - Pereira, Ralmon Sousa (2020)
This research investigated efficient means to make use of free plugins for young entrepreneurs and their Home Studio projects. In order to put that into practice, the Linux Mint operating system (optimized for professional audio) and DAW Ardour (host), have been chosen. To achieve the results, two research approaches have been applied: A systematic review and the mixing of the album recorded by the Grupo de Metais Nordeste (GMNE), performed exclusively inside the computer (also known in the pro audio industry as "mix in the box"). The whole mixing process was based on the The Art of Mixing concept of David Gibson. The CALF Plugin Kits, EQ10Q Lv2, and others learned during the course of the research, resulted in a mixing process containing 100% free tools, demonstrating its efficiency ranging from simple processes to advanced mixing techniques.